Simulation of Service Queue for Dental Doctor Patients at Kindergarten Hospital. IV 01.07.02 Binjai Using the Exponential Method - Br Bangun, Cindy Arsita; Pardede, A M H; Sihombing, Marto (Yayasan Kita Menulis, 2024)
One of the systems that can be simulated is a queue. The queuing system consists of a collection of customer servers, a queue that regulates service to customers. The utilization of queuing simulations is to optimize services by designing service resources so that services can be effective and efficient. In the queuing system there are several problems that often occur, for example queuing queues, the number of queues will cause problems such as bored customers, and discomfort will make customers dissatisfied with the service. The Application of the Exponensial Method in the Dentist Patient Service Queuing System There are 28 general populations in this study, namely all consumers at the Kesrem Binjai Hospital, while the target population is the population that is actually used as a data source for patients who queue at the Kesrem Binjai Hospital to get the best service. is the target population in this study.